62 Evaluating detoxification efficacy of deoxynivalenol by encapsulated sodium metabisulfite (SMBS) using an in vitro intestinal epithelial cell IPEC-J2 model. (30th November 2020) - Lu, Peng; Yu, Changning; Liu, Shangxi; Gong, Joshua; Liu, Song; Yang, Chengbo
Abstract: Deoxynivalenol (DON) contamination occurs on feed ingredients and causes a reduction in growth performance, damage to the intestinal epithelial cells, and increased susceptibility to enteric pathogen challenge. Sodium metabisulfite (SMBS) has been successfully used to destroy DON in processed grains or feeds. However, SMBS degrades quickly under aqueous acid conditions, such as pig stomachs, and when SMBS is added to diet, little will remain intact in the small intestine where an optimal pH environment exists for detoxification by SMBS. Thus, this study was to encapsulate SMBS into microparticles to deliver intact SMBS to the small intestine and evaluate its efficacy of DON detoxification in the simulated intestine fluid (SIF) using an in vitro intestinal epithelial cell (IPEC-J2) model. The results showed that around 40% of the SMBS loading capacity was achieved in the microparticles. In vitro release studies showed that 1.61% of encapsulated SMBS was released in the simulated gastric fluid (SGF), and the majority of encapsulated SMBS (75.52%) was progressively released in the SIF within 6 h at 37 °C. In vitro cell experiments showed that DON treated with the SIF containing 0.5% SMBS for 2 h completely attenuated the DON-induced cytotoxicity. When DON was treated with the SGF containing 0.5% encapsulated SMBS for 2 h and then the mixture was mixed with the SIF (1:1) and incubated for 2 h, it also completely attenuated the DON-induced cytotoxicity. Moreover, DON treated with the simulated fluid containing 0.5% encapsulated SMBS completely attenuated the gene expression inflammatory cytokines upregulated by DON and restored trans-epithelial electrical resistance (TEER) and tight junction and cytoskeleton. In summary, the encapsulation of SMBS was stable in SGF and allowed a progressive release of SMBS in the SIF. Moreover, the released SMBS in the SIF effectively attenuated the adverse effects induced by DON in the intestinal epithelial cells.